Preventive aspects in children’s caries treatments preceding dental care under general anaesthesia - NORA SAVANHEIMO (IAPD and Blackwell, 2008)
The most common indications for children’s dental care under general anaesthesia (GA) are the extensive need of dental treatments, the presence of dental fear or problems related to general health, conditions following extensive orofacial or dental trauma, and noncooperation due to a child’s young age in the treatment of early childhood caries 1–5 . For adolescents, untreated severe tooth decay is largely a consequence of long-term avoidance of dental care